Seduction, deception and technology. Issue 1 (17th December 2022) - Tyler, Susan
Abstract: This paper proposes that exploring the use of internet pornography creates a potentially beneficial, albeit defensive liminal space that can be used therapeutically. The content of compelling sexual scenes can be viewed as the psyche's way of mastering internal trauma and masking an inner emptiness. However, from a Jungian perspective, the use of internet pornography can also be seen as a patient's distorted way of trying to make dissociated affects more bearable by triumphing over them. The sexual use of technology can express intrapsychic conflict encapsulated in what Stoller called 'microdots'. Stoller's microdots are unique scripts – a kind of emotional code that gives clinicians an opportunity to reveal unconscious processes and transcend them through meaning making. Wood's work at the Portman Clinic on the chosen 'compelling scenarios' of pornography‐addicted patients is also examined with this Jungian lens. Jung's idea of the transcendent function is used to show the value of holding the tension of fantasy and frustration provoked by intimacy. The paper illustrates how they come together within the therapeutic relationship to stimulate something new. Abstract : Cet article suggère qu'étudier l'utilisation de la pornographie sur internet crée un espace potentiellement bénéfique, même s'il est défensif, et qui peut être utilisé de manière thérapeutique. Le contenu de scènes sexuelles impressionnantes peut être compris comme la manière dont la psyché maitrise le traumatisme interne et masque le vide intérieur. Mais d'un point de vue Jungien, l'utilisation de la pornographie sur internet peut également être pensée comme la manière, certes perturbée, du patient pour tenter de rendre plus supportables des affects dissociés en prenant le dessus sur ces fameux affects. L'utilisation sexuelle de la technologie peut exprimer le conflit intrapsychique encapsulé dans ce que Stoller a appelé les 'micropoints'. Les micropoints de Stoller sont des scénarios uniques – une sorte de code émotionnel qui donne aux cliniciens l'occasion de révéler les processus inconscients et de les transcender en y donnant du sens. Le travail de Wood à la Portman Clinic – sur les 'scénarios fascinants' des patients dépendants à la pornographie – est également étudié à travers la perspective Jungienne. L'idée Jungienne de la fonction transcendante est utilisée pour montrer qu'il est précieux de tenir la tension entre fantasme et frustration, tension qui provient de l'intimité. Cet article illustre comment ils se rejoignent dans la relation thérapeutique pour stimuler quelque chose de nouveau. Abstract : In diesem Aufsatz wird der Vorschlag unterbreitet, daß die Erforschung der Verwendung von Internetpornographie einen potentiell vorteilhaften, wenn auch defensiven Grenzraum schafft, der therapeutisch genutzt werden kann. Der Inhalt animierender Sexszenen kann als Mittel der Psyche angesehen werden, ein inneres Trauma zu bewältigen und eine innere Leere zu maskieren. Aus einer Jungianischen Perspektive heraus kann der Gebrauch von Internetpornographie jedoch auch als verzerrter Versuch eines Patienten angesehen werden, dissoziierte Affekte erträglicher zu machen, indem er über sie triumphiert. Der sexuelle Gebrauch von Technologie kann intrapsychische Konflikte ausdrücken, die in dem verkapselt sind, was Stoller 'Mikropunkte' nannte. Stollers Mikropunkte sind einzigartige Skripte – eine Art emotionaler Code, der Klinikern die Möglichkeit gibt, unbewußte Prozesse aufzudecken und sie durch Sinnstiftung zu transzendieren. Woods Arbeit an der Portman Clinic zu den ausgewählten 'zwingenden Szenarien' von pornographiesüchtigen Patienten wird ebenfalls mit Hilfe dieser Jungianischen Linse untersucht. Jungs Idee der transzendenten Funktion wird verwendet, um den Wert aufzuzeigen der darin besteht, die durch Intimität hervorgerufene Spannung von Fantasie und Frustration aufrechtzuerhalten. Der Beitrag veranschaulicht, wie beide in der therapeutischen Beziehung zusammenkommen, um etwas Neues anzuregen. Abstract : Questo articolo suggerisce che l'esplorazione dell'uso della pornografia online crei uno spazio liminale potenzialmente benefico, seppur difensivo, che può essere usato terapeuticamente. Il contenuto di scene sessuali coinvolgenti può essere visto come il tentativo della psiche di padroneggiare il trauma interno e mascherare un vuoto interiore. Tuttavia, da una prospettiva junghiana, l'utilizzo della pornografia online può anche essere visto come il modo distorto del paziente per cercare di rendere più sopportabili gli affetti dissociati trionfando su di essi. L'uso sessuale della tecnologia può esprimere un conflitto intrapsichico racchiuso in quelli che Stoller chiama 'micropunti'. I micropunti di Stoller sono degli scritti unici ‐ un tipo di codice emotivo che offre agli specialisti un'opportunità per individuare i processi inconsci e trascenderli tramite la creazione di significati. Anche il lavoro di Wood presso la clinica Portman sugli 'scenari avvincenti' scelti dai pazienti dipendenti dalla pornografia viene esaminato con queste lente junghiana. L'idea di Jung della funzione trascendente viene usata per mostrare il valore del tenere la tensione della fantasia e la frustrazione provocata dall'intimità. L'articolo illustra come questi confluiscono all'interno della relazione terapeutica per stimolare qualcosa di nuovo. Abstract : В статье предполагается, что исследование обращения к интернет‐порнографии создает потенциально полезное, хотя и защитное лиминальное пространство, которое может быть использовано в терапевтических целях. В содержании навязчивых сексуальных сцен можно видеть попытки психики справиться с внутренней травмой и замаскировать внутреннюю пустоту. Однако, с точки зрения Юнга, обращение пациента к интернет‐порнографии можно также рассматривать как уродливые попытки сделать диссоциированные аффекты более переносимыми, одержав над ними победу. Использование технологий в сексуальных целях может быть манифестацией интрапсихического конфликта, выраженного посредством того, что Столлер назвал "микроточками". Микроточка, по Столлеру ‐ это уникальный сценарий, своего рода эмоциональный код, с помощью которого клиницисты имеют возможность выявлять бессознательные процессы и справляться с ними путем создания смысла. Предлагается юнгианский взгляд на исследование выборки «навязчивых сценариев» у пациентов с порнографической зависимостью, выполненное Вудом в клинике Портмана. Важность удерживания напряжения между фантазией и фрустрацией, провоцируемыми близостью, обосновывается с помощью юнговской концепции трансцендентной функции. В статье показано, как они соединяются в терапевтических отношениях, что стимулирует возникновение чего‐то нового. Abstract : El presente trabajo propone que la exploración del uso de pornografía por internet crea un beneficio potencial, aún siendo un espacio liminal defensivo, que puede ser usado terapéuticamente. El contenido de atractivas escenas sexuales puede percibirse como el modo de la psique de dominar el trauma interno y de enmascarar el vacío interior. Sin embargo, desde una perspectiva Junguiana, el uso de pornografía por internet puede considerarse como un modo distorsionado del paciente de tratar de hacer más tolerables emociones disociadas triunfando sobre las mismas. El uso sexual de tecnología puede expresar conflicto intrapsíquico encapsulado en lo que Stoller llamó `micropuntos`. Los `micropuntos`de Stoller son guiones únicos – una especie de código emocional que le da al clínico una oportunidad para revelar procesos inconscientes y trascenderlos a través de darles sentido. También se examina con este lente Junguiano el trabajo de Wood en la Clínica Portman sobre los elegidos `escenarios cautivantes` de pacientes con adicción a la pornografía. La idea de Jung sobre la Función Trascendente es utilizada para mostrar el valor de sostener la tensión entre fantasía y frustración provocada por la intimidad. El trabajo ilustra cómo ambas coinciden en la relación terapéutica para estimular algo nuevo. Abstract : 诱惑、欺骗和技术 本文提出, 对互联网色情制品的使用的探索, 可以创造了一个潜在的获益, 虽说那是个防御性的边缘空间, 但仍可以被用于治疗。令人信服的性爱场景的内容, 可以被视为心灵的一种对内在创伤获得掌控的方式, 以及遮掩内在空洞的方式。然而, 从荣格的角度来看, 使用网络色情制品也可以被看作是病人试图通过一种扭曲的方式, 来战胜被解离的情感, 从而使它们更可容忍。技术在性上的使用, 可以表达一种心理内部的冲突, 它被封装在斯托勒称之为 "微点 "地方的。斯托勒的微点是一个独特的脚本——它是一种情感代码, 使临床医生有机会揭示无意识的过程, 并通过意义创造来超越它们。 文章还从荣格的视角来审视伍德在波特曼诊所所做的工作, 即对色情成瘾患者所选择的 "引人注目的场景 "所做的工作。荣格的超越功能的想法被用来表明, 抱持住幻想的张力和由亲密关系引发的挫折的价值。本文说明了它们是如何在治疗关系中结合在一起以激发新的东西。